Depressive Symptoms after Hospitalization in Older Adults: Function and Mortality Outcomes - Pierluissi, Edgar (2012)
OBJECTIVES: To determine the relationship between depressive symptoms after hospitalization and survival and functional outcomes. DESIGN: Secondary analysis of a prospective cohort study SETTING: General medical service of two urban, teaching hospitals in Ohio PARTICIPANTS: Hospitalized patients, age 70 years or older. MEASUREMENTS: We measured 10 depressive symptoms, instrumental activities of daily living (IADL), and basic activities of daily living (ADL) at hospital discharge and 1, 3, 6, and 12 months later. Using all data points, we determined subject-specific changes in depressive symptoms (slopes). We also defined four groups according to the number of depressive symptoms (≤3 symptoms, Low; 4–10 symptoms, High) at discharge and follow-up: Low-Low, Low-High, High-Low, and High-High. We measured mortality at 3, 6, and 12 months after hospital discharge. RESULTS: Both subject-specific discharge depressive symptoms and change in depressive symptoms over time (slopes) were associated (P<0.05) with functional and mortality outcomes. At 1 year, more patients in the Low-Low depressive symptom group were alive and independent in instrumental activities of daily living (IADL) and basic activities of daily living (ADL), compared to the Low-High group (49% vs 37%, P=0.02).and more patients in the High-Low group were alive and independent in IADL and ADL, compared to the High-High group (39% vs 19%, P<0.001). CONCLUSION: Both the number of depressive symptoms and the change in the number of depressive symptoms during the year after discharge were associated with functional and mortality outcomes in hospitalized older adults. Fewer patients with persistently high or increasing depressive symptoms after hospitalization were alive and functionally independent 1 year later than patients with decreasing or persistently low symptoms, respectively.